PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SERTA PERILAKU GIZI SEIMBANG IBU KAITANNYA DENGAN STATUS GIZI DAN KESEHATAN BALITA DI KABUPATEN BOJONEGORO, JAWA TIMUR - Linda Dwi Jayanti; Yekti Hartati Effendi; Dadang Sukandar (Jurnal Gizi dan Pangan, 2011)
The purpose of this study was to determine nutritional knowledge, clean and healthy lifestyle behavior, and balanced diet on maternal behavior, as well as its relationship with nutritional and health status and children under 5 years health. The cros sectional study was conducted during March-April 2011. The population in this study consist of all the children under five living in Campurejo village, Bojonegoro districts East Java Province. The respondents were mothers of toddlers who were selected as samples. Total samples in this study were 55 toddlers. The results showed that maternal nutrition knowledge is positively correlated with clean and healthy lifestyle behavior (pKey words: e.